UK’s Turing Scheme: The Challenges Ahead - Guibert, José; Rayón, Alex (International Higher Education, 2021)
Brexit supporters did not like the Erasmus student mobility exchange program. During the past three decades, Erasmus has helped students, especially those from low-income backgrounds who are the least likely to travel internationally, to gain better employment and improve their skills thanks to their study abroad experiences. Will the new Turing scheme, devised by the British government, be able to provide students with the same benefits?